EXPLORING THE ROLE OF MOTIVATION IN ENHANCING UNIVERSITY STUDENTS’ ORAL PERFORMANCE IN EFL CLASSROOMS - Fitra Ramadhani; Muhammad Arbain; Hartatya Novika (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2020)
This research is intended to find out the factors influencing the university students’ motivation in learning English speaking skill, and the efforts carried out to motivate the university students to speak English. The design employed in this research report belongs to descriptive research. The result of research finding concerning with some factors influencing the university students’ motivation in learning English speaking skill shows that students’ age gender has the highest percentage (97%), frequency of attendance and degree of students’ interest to oral expression (89%) and Students’ gender distribution(81%), whereas particularly dealing with students’ opinions about the most used teaching strategies (‘using materials (videos and music)’ and ‘group/pair work’) has the lowest percentage (21%). Meanwhile the result of research finding concerning with the strategies carried out to motivate the university students to speak English, degree of teaching strategies’ use has the highest percentage (99.9%).